Studying abroad: the change does not stop when students come home - Roberts, Kimberly L. (Kansas State University, 2012)
Study abroad participation has grown throughout the years at a steady pace (Chow & Bhandari, 2011; Fischer, 2011; Rhodes, Biscarra, Loberg, & Roller, 2012). A length of stay can range from a few weeks to a year. A high majority of students who have experienced study abroad have changed in some way throughout their stay, but what about when they return to the United States? What other changes do students go through and experience when they come home? The change simply does not stop once a student comes home from studying abroad. This report discusses the various transitions students go through when they go abroad, but also what student affairs professionals can do to help students get through the process of change and acclimation back in the university. Conversations with students who have studied abroad and professionals in study abroad will be referred to throughout the paper. The students were chosen based on their experiences abroad and their willingness to participate. Personal experiences will also be utilized by the author to provide perspective of the experience of reentry to the readers. Research highlighted the benefits of going abroad are broad (Dwyer & Peters, 2004; Sutton & Rubin, 2010). However, the reentry phase back to the United States is an area yet to be thoroughly studied. Through a review of past literature and conversations with professionals and participants in study abroad, it is clear that a reentry model needs to be implemented so that students can be assisted in a more helpful manner. As part of this report, a reentry model will be discussed and will include specific suggestions to assist students with the reentry process.
Keywords: Study abroad; Reentry; Higher Education (0745); International Relations (0601)